Cultural psychology – new challenge or perspective of psychology - Dudek, Zenon Waldemar; Pankalla, Andrzej (Studia Psychologica: Theoria et praxis, 2007)
The naturalistic methodology is responsible for the domination of psychobiological model of man in modern psychology. Other option is the social model of psyche, but it express the tendency to interprete a human being as regulated rather by external (social, biological) then by personal norms. Both concerned models need external and objective facts (data) and statistical, quantitative evaluation and depreciate the qualitative observation or interpretation. The authors present the opinion that the cultural psychology is the model, which tends to explore the psychic phenomena as qualitative and individual (personal history, subjective experience, self-consciousness) and in the context of cultural and psychological identity. Modern psychology has to confront the issue of global consciousness. The inter-, trans- and multicultural processes involve psychological functions of the man. The cultural psychology has to study inter-cultural and trans-cultural phenomena and their influence on the psyche. Cultural and personal myths are symbolic base for creating narrative identity of the individual and as inner, personal story they reflect the ontological relation psyche – culture. The questions addressed to cultural psychology: cultural conditions of therapeutic process, spiritual (liminal, subliminal, trans-cultural) experience, archetypal dreams, new shamanism, new spiritual movements, virtual worlds, medial communication in the trans-cultural context etc. The inspirations for cultural psychology are in the field of psychology, philosophy, anthropology, sociology (W. Wundt, L. Wygotsky, C.G. Jung, H.A. Murray, J.S. Bruner, R. May, L. Lévy-Bruhl, N. Frye, J. Campbell, E. Goffman, R. Linton). The important role plays the idea of transculturality (W. Welsch) and theories rooted in depth psychology (theory of archetypes – C.G. Jung, E. Neumann, J. Hillman, M.-L. von Franz, V. Kast, A. Samuels, O. Vedfelt), narrative psychology (the concept of personal myth, narrative identity - D. McAdams, S. Keen, K. Gergen), ethnological psychology (entheogenes - J.M. Fericgla), historical psychology (M. Cole, C. Ratner, R. Shweder, E. Boesch, J. Vaalsiner). In Poland the interest in cultural psychology is growing up year by year.